2016
DOI: 10.1111/ijsw.12200
|View full text |Cite
|
Sign up to set email alerts
|

The differential role of human capital and health in explaining welfare exit‐route and labour outcomes

Abstract: Achdut N. The differential role of human capital and health in explaining welfare exit-route and labour outcomesThe aim of this study was to determine the differential effects of human capital and health on welfare exit-route, earnings and working hours among female welfare recipients in Israel. The study also examined whether higher human capital mediates the effect of health problems on the different outcomes. The data were obtained from a national panel survey of 2,700 single mothers who were receiving welf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…A large body of research has found that wages grow with work experience and that prolonged periods of unemployment lower women's wages (see Grogger, 2009;Loeb & Corcaran, 2001). Several studies with welfare recipients in focus have yielded similar findings (Achdut, 2016;Loeb & Corcaran, 2001;Noonan & Heflin, 2005). Other studies (Card & Hyslops, 2005;Dustmann & Meghir, 2005), however, found that there was little wage growth with work experience for welfare recipients and other lowskilled workers.…”
Section: 'Making Work Pay' In Practicementioning
confidence: 70%
“…A large body of research has found that wages grow with work experience and that prolonged periods of unemployment lower women's wages (see Grogger, 2009;Loeb & Corcaran, 2001). Several studies with welfare recipients in focus have yielded similar findings (Achdut, 2016;Loeb & Corcaran, 2001;Noonan & Heflin, 2005). Other studies (Card & Hyslops, 2005;Dustmann & Meghir, 2005), however, found that there was little wage growth with work experience for welfare recipients and other lowskilled workers.…”
Section: 'Making Work Pay' In Practicementioning
confidence: 70%
“…The analysis will focus on the mothers' labour market behaviour and how their employment contributes to the ending of benefit receipt. general or have defined employment-related exits as one possible route among others (i.e., Achatz & Trappmann 2011;Achdut 2016;Bane & Ellwood 1986;Buhr 1995;Leisering & Leibfried 1999;Gangl 1998;Graf and Rudolph 2009;Schels 2011). This research has shown for Germany that single mothers have particularly low chances to end benefit receipt (Buhr 1995;Graf and Rudolph 2009).…”
Section: Introductionmentioning
confidence: 93%
“…These decisions are taken in light of individual resources and constraints. In the case of mothers in benefit receipt their additional employment in the household is one way to improve the financial situation of low-income households (Andress 1999). Constraints on their labour market behaviour should be situated in the household context and the associated childcare responsibilities as well as the extended social environment such as the structure of the labour market for women and public childcare infrastructure.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%
“…A human capital model suggests that recipients will exit income support and welfare systems when they have the appropriate work skills, experience, and education they need to obtain jobs that pay them more than they can make on income benefits (Achdut, 2016). However, existing research on factors that support welfare system exits is mixed (Jones et al, 2014), highlighting the complexity involved.…”
mentioning
confidence: 99%
“…However, this approach has been shown to be ineffective in increasing long-term employment outcomes (Webster, 2016). In fact, there is evidence to suggest that successful long-term employment outcomes are even more remote for recipients who get established on disability benefits (Achdut, 2016;Gewurtz et al, 2015b;Kinn et al, 2014). Furthermore, sustained employment is not possible without first stabilizing the illness.…”
mentioning
confidence: 99%